PENGARUH LINGKUNGAN KERJA, MOTIVASI DAN KEPUASAN TERHADAP KINERJA KARYAWAN DIVISI MALL OPERATIONAL DI MALL PACIFIC PLACE JAKARTA - Aris Budiono; Anita Charoline (LPPM Universitas Asa Indonesia, 2019)
Purpose- This study aims to analyze the influence of the work environment, motivation, and satisfaction on employee performance both partially and simultaneously at Mall Pacific Place Jakarta. Design/methodology/approach- In this sample research respondents used were Pacific Place Jakarta employees consisting of 97 respondents, by saturated technique. The analysis technique uses multiple linear regression. Findings- Found the influence of work environment variables with employee performance is 2,80% meaning there is a real but weak relationship between work environment variables with partial performance, the effect of motivation variables with employee performance is 10,90% meaning there is a real relationship but moderate between motivation variables with partial employee performance, the effect of satisfaction variables with employee performance is 7,41% meaning that there is a real but weak relationship between satisfaction variables with employee performance partially, in conclusion the work environment, motivation and satisfaction simultaneously have a significant effect on Pacific Place Jakarta namely 36,97%, and the rest is influenced by other factors not explained in this study.